Plastic bottle with high heat resistance and preparation method thereof
Through the raw materials and processing technology with specific ratios, the problems of poor compressive strength, toughness and heat resistance of existing plastic bottles are solved, and the preparation of high-heat resistance plastic bottles is realized, which significantly improves the performance and use efficiency of the product.
Patent Information
- Application Number
- CN202411990805.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
The existing plastic bottles have poor compressive strength, toughness and antibacterial properties, and poor thermal resistance and stability, which limit the efficiency of the product.
The raw materials with specific ratios, including linear low-density polyethylene, recycled plastic raw materials, modified plant fibers, antibacterial agents, antioxidants, epoxy soybean oil and modified nanotitanium dioxide, are molded by extrusion granulation and hot air blow molding.
It significantly improves the compressive strength, toughness and heat resistance of plastic bottles, enhances antibacterial properties, and extends the service life of the product.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic bottles, and in particular to a high-heat-resistant plastic bottle and a preparation method thereof. Background Art
[0002] Plastic bottles are mainly made of materials such as polyethylene or polypropylene and added with a variety of organic solvents. Plastic bottles widely use polyester (PET), polyethylene (PE), and polypropylene (PP) as raw materials. After adding corresponding organic solvents, they are heated at high temperatures and blow-molded, extruded, or injection-molded through plastic molds. They are mainly used for liquid or solid disposable plastic packaging containers such as beverages, foods, pickles, honey, dried fruits, edible oils, and agricultural and veterinary drugs. Plastic bottles have the characteristics of being not easy to break, low cost, high transparency, and food-grade raw materials.
[0003] The existing rate bottles have poor compressive strength, toughness and antibacterial properties. It is difficult to achieve coordinated improvements in compressive strength and toughness. At the same time, the product's heat resistance stability is poor, which limits the product's use efficiency. Summary of the invention
[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a high heat-resistant plastic bottle and a preparation method thereof to solve the problems raised in the above background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution: The present invention provides a high heat-resistant plastic bottle, comprising the following raw materials in parts by weight: 30-35 parts of linear low-density polyethylene, 25-30 parts of recycled plastic raw materials, 10-15 parts of modified plant fibers, 4-7 parts of antibacterial agents, 2-5 parts of antioxidants, 2-4 parts of epoxidized soybean oil, and 3-6 parts of modified nano titanium dioxide.
[0006] Preferably, the plastic bottle comprises the following raw materials in parts by weight: 30-35 parts of linear low-density polyethylene, 25-30 parts of recycled plastic raw materials, 10-15 parts of modified plant fibers, 4-7 parts of antibacterial agents, 2-5 parts of antioxidants, 3 parts of epoxidized soybean oil, and 3-6 parts of modified nano titanium dioxide.
[0007] Preferably, the linear low-density polyethylene has a melt index of (20-80) g / 10 min at 190° C. and 2.16 kg; the antibacterial agent is nano silver powder; The recycled plastic raw material is waste plastic that has been recycled, then treated in a 5% by mass acid solution for 2 hours, then washed with boiling water for 3 times, and then crushed to 100 mesh; the antioxidant is antioxidant 1010; Preferably, the preparation method of the modified plant fiber is: S1: adding 2-5 parts of nano magnesium oxide, 2-3 parts of boron nitride and 1-2 parts of calcium stearate to 5-8 parts of chitosan solution and stirring evenly to obtain nano magnesium oxide liquid; Plant fibers are added to nano magnesium oxide in a weight ratio of 2:5 and stirred to obtain a fiber-modified calcium carbonate solution; S2: The fiber-modified calcium carbonate solution and the co-mixing agent are mixed in a weight ratio of 5:3, and the mixture is ball-milled at a speed of 1500 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain the modified plant fiber.
[0008] Preferably, the mass fraction of the chitosan solution is 2-5%; the stirring speed of the stirring treatment is 450-550 r / min, and the stirring time is 20-30 min; and the plant fiber is bamboo fiber.
[0009] Preferably, the preparation method of the synergistic agent is: The silicon micropowder is immersed in a dopamine hydrochloride solution which is 2-4 times the total amount of the silicon micropowder to obtain a silicon micropowder liquid. The silicon micropowder liquid, tourmaline powder and sodium silicate solution are mixed in a weight ratio of 3:1:2 and ball-milled at a speed of 1500 r / min for 1 hour. After the ball-milling is completed, the mixture is filtered and dried to obtain a synergistic agent.
[0010] Preferably, the mass fraction of the dopamine hydrochloride solution is 2-5%; the mass fraction of the sodium silicate solution is 3-5%.
[0011] Preferably, the modification method of the modified nano titanium dioxide is: S11: adding 1-2 parts of silane coupling agent KH550, 2-3 parts of hydroxyapatite and 1-2 parts of sodium carboxymethyl cellulose to 5-6 parts of lanthanum chloride solution and stirring thoroughly, and then completing the stirring to obtain a modified solution; S12: The nano-titanium dioxide and the modified liquid are stirred and modified at a weight ratio of 2:5, the stirring temperature is 60-65° C., the stirring time is 1 hour, the stirring speed is 450-500 r / min, and after the stirring is completed, the mixture is filtered and dried to obtain the modified nano-titanium dioxide.
[0012] Preferably, the mass fraction of the lanthanum chloride solution is 4-6%.
[0013] The present invention also provides a method for preparing a high heat-resistant plastic bottle, comprising the following steps: mixing the raw materials, then extruding and granulating them at an extrusion temperature of 165°C, and then blow molding them at a temperature of 120°C using a hot air blow molding method to obtain a high heat-resistant plastic bottle.
[0014] Compared with the prior art, the present invention has the following beneficial effects: The technology of the present invention relates to the field of plastic processing, including preparing mixed polyethylene, recycled plastic raw materials, plant fibers and other raw materials, and improving the compressive strength, toughness, heat resistance and antibacterial properties of plastic bottles through specific ratios and processing steps to avoid deterioration of the contained materials. At the same time, the plant fibers are modified and then matched with modified nano titanium dioxide. At the same time, the performance of the product is further improved through the blending and coordination of the two. The modified plant fibers are blended and improved by blending the plant fibers with nano magnesium oxide liquid, and then ball milled and coordinated with a co-mixing agent to optimize the performance effect of the product. At the same time, the nano titanium dioxide is improved by the modified liquid, and the raw materials in the modified liquid are blended and coordinated, so that the performance of the product is further improved. DETAILED DESCRIPTION
[0015] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0016] A high heat-resistant plastic bottle of this embodiment includes the following raw materials in parts by weight: 30-35 parts of linear low-density polyethylene, 25-30 parts of recycled plastic raw materials, 10-15 parts of modified plant fibers, 4-7 parts of antibacterial agents, 2-5 parts of antioxidants, 2-4 parts of epoxidized soybean oil, and 3-6 parts of modified nano titanium dioxide.
[0017] The plastic bottle of this embodiment includes the following raw materials in parts by weight: 30-35 parts of linear low-density polyethylene, 25-30 parts of recycled plastic raw materials, 10-15 parts of modified plant fibers, 4-7 parts of antibacterial agents, 2-5 parts of antioxidants, 3 parts of epoxidized soybean oil, and 3-6 parts of modified nano titanium dioxide.
[0018] The linear low-density polyethylene of this embodiment has a melt index of (20-80) g / 10 min at 190° C. and 2.16 kg; the antibacterial agent is nano silver powder; The recycled plastic raw material is waste plastic that has been recycled, then treated in a 5% by mass acid solution for 2 hours, then washed with boiling water for 3 times, and then crushed to 100 mesh; the antioxidant is antioxidant 1010; The preparation method of the modified plant fiber of this embodiment is: S1: adding 2-5 parts of nano magnesium oxide, 2-3 parts of boron nitride and 1-2 parts of calcium stearate to 5-8 parts of chitosan solution and stirring evenly to obtain nano magnesium oxide liquid; Plant fiber is added into nano magnesium oxide in a weight ratio of 2:5 and stirred to obtain fiber-polyhydrated calcium carbonate solution; the plant fiber is bamboo fiber; S2: The fiber-modified calcium carbonate solution and the co-mixing agent are mixed in a weight ratio of 5:3, and the mixture is ball-milled at a speed of 1500 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain the modified plant fiber.
[0019] The mass fraction of the chitosan solution in this embodiment is 2-5%; the stirring speed of the stirring treatment is 450-550 r / min, and the stirring is performed for 20-30 min.
[0020] The preparation method of the synergistic agent of this embodiment is: The silicon micropowder is immersed in a dopamine hydrochloride solution which is 2-4 times the total amount of the silicon micropowder to obtain a silicon micropowder liquid. The silicon micropowder liquid, tourmaline powder and sodium silicate solution are mixed in a weight ratio of 3:1:2 and ball-milled at a speed of 1500 r / min for 1 hour. After the ball-milling is completed, the mixture is filtered and dried to obtain a synergistic agent.
[0021] The mass fraction of the dopamine hydrochloride solution in this embodiment is 2-5%; the mass fraction of the sodium silicate solution is 3-5%.
[0022] The modification method of the modified nano titanium dioxide in this embodiment is: S11: adding 1-2 parts of silane coupling agent KH550, 2-3 parts of hydroxyapatite and 1-2 parts of sodium carboxymethyl cellulose to 5-6 parts of lanthanum chloride solution and stirring thoroughly, and then completing the stirring to obtain a modified solution; S12: The nano-titanium dioxide and the modified liquid are stirred and modified at a weight ratio of 2:5, the stirring temperature is 60-65° C., the stirring time is 1 hour, the stirring speed is 450-500 r / min, and after the stirring is completed, the mixture is filtered and dried to obtain the modified nano-titanium dioxide.
[0023] The mass fraction of the lanthanum chloride solution of the present embodiment is 4-6%.
[0024] The method for preparing a high heat-resistant plastic bottle of the present embodiment comprises the following steps: mixing the raw materials, then extruding and granulating them at an extrusion temperature of 165°C, and then blow molding them at a temperature of 120°C using hot air blow molding to obtain a high heat-resistant plastic bottle.
[0025] Example 1. A high heat-resistant plastic bottle of this embodiment includes the following raw materials in parts by weight: 30 parts of linear low-density polyethylene, 25 parts of recycled plastic raw materials, 10 parts of modified plant fibers, 4 parts of antibacterial agents, 2 parts of antioxidants, 2 parts of epoxidized soybean oil, and 3 parts of modified nano titanium dioxide.
[0026] The linear low-density polyethylene of this embodiment has a melt index of 20 g / 10 min at 190° C. and 2.16 kg; the antibacterial agent is nano silver powder; The recycled plastic raw material is waste plastic that has been recycled, then treated in a 5% by mass acid solution for 2 hours, then washed with boiling water for 3 times, and then crushed to 100 mesh; the antioxidant is antioxidant 1010; The preparation method of the modified plant fiber of this embodiment is: S1: adding 2 parts of nano magnesium oxide, 2 parts of boron nitride and 1 part of calcium stearate to 5 parts of chitosan solution and stirring evenly to obtain nano magnesium oxide liquid; Plant fibers are added to nano magnesium oxide in a weight ratio of 2:5 and stirred to obtain a fiber-modified calcium carbonate solution; S2: The fiber-modified calcium carbonate solution and the co-mixing agent are mixed in a weight ratio of 5:3, and the mixture is ball-milled at a speed of 1500 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain the modified plant fiber.
[0027] The mass fraction of the chitosan solution in this embodiment is 2%; the stirring speed of the stirring process is 450 r / min, and the stirring is performed for 20 minutes.
[0028] The preparation method of the synergistic agent of this embodiment is: The silicon micropowder is immersed in a dopamine hydrochloride solution with an amount twice that of the total amount of the silicon micropowder to obtain a silicon micropowder liquid. The silicon micropowder liquid, tourmaline powder and sodium silicate solution are mixed in a weight ratio of 3:1:2 and ball-milled at a speed of 1500 r / min for 1 hour. After the ball-milling is completed, the mixture is filtered and dried to obtain a synergistic agent.
[0029] The mass fraction of the dopamine hydrochloride solution in this embodiment is 2%; the mass fraction of the sodium silicate solution is 3%.
[0030] The modification method of the modified nano titanium dioxide in this embodiment is: S11: adding 1 part of silane coupling agent KH550, 2 parts of hydroxyapatite and 1 part of sodium carboxymethyl cellulose to 5 parts of lanthanum chloride solution and stirring thoroughly, and the stirring is completed to obtain a modified solution; S12: The nano-titanium dioxide and the modified liquid are stirred and modified in a weight ratio of 2:5, the stirring temperature is 60° C., the stirring time is 1 hour, the stirring speed is 450 r / min, and after the stirring is completed, the mixture is filtered and dried to obtain modified nano-titanium dioxide.
[0031] The mass fraction of the lanthanum chloride solution of the present embodiment is 4%.
[0032] The method for preparing a high heat-resistant plastic bottle of the present embodiment comprises the following steps: mixing the raw materials, then extruding and granulating them at an extrusion temperature of 165°C, and then blow molding them at a temperature of 120°C using hot air blow molding to obtain a high heat-resistant plastic bottle.
[0033] Example 2. A high heat-resistant plastic bottle of this embodiment includes the following raw materials in parts by weight: 35 parts of linear low-density polyethylene, 30 parts of recycled plastic raw materials, 15 parts of modified plant fibers, 7 parts of antibacterial agents, 5 parts of antioxidants, 4 parts of epoxidized soybean oil, and 6 parts of modified nano titanium dioxide.
[0034] The linear low-density polyethylene of this embodiment has a melt index of 80 g / 10 min at 190° C. and 2.16 kg; the antibacterial agent is nano silver powder; The recycled plastic raw material is waste plastic that has been recycled, then treated in a 5% by mass acid solution for 2 hours, then washed with boiling water for 3 times, and then crushed to 100 mesh; the antioxidant is antioxidant 1010; The preparation method of the modified plant fiber of this embodiment is: S1: adding 5 parts of nano magnesium oxide, 3 parts of boron nitride and 2 parts of calcium stearate to 8 parts of chitosan solution and stirring evenly to obtain nano magnesium oxide liquid; Plant fibers are added to nano magnesium oxide in a weight ratio of 2:5 and stirred to obtain a fiber-modified calcium carbonate solution; S2: The fiber-modified calcium carbonate solution and the co-mixing agent are mixed in a weight ratio of 5:3, and the mixture is ball-milled at a speed of 1500 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain the modified plant fiber.
[0035] The mass fraction of the chitosan solution in this embodiment is 5%; the stirring speed of the stirring process is 550 r / min, and the stirring is performed for 30 minutes.
[0036] The preparation method of the synergistic agent of this embodiment is: The silicon micropowder is immersed in a dopamine hydrochloride solution which is 4 times the total amount of the silicon micropowder to obtain a silicon micropowder liquid. The silicon micropowder liquid, tourmaline powder and sodium silicate solution are mixed in a weight ratio of 3:1:2 and ball-milled at a speed of 1500 r / min for 1 hour. After the ball milling is completed, the mixture is filtered and dried to obtain a synergistic agent.
[0037] The mass fraction of the dopamine hydrochloride solution in this embodiment is 5%; the mass fraction of the sodium silicate solution is 5%.
[0038] The modification method of the modified nano titanium dioxide in this embodiment is: S11: adding 2 parts of silane coupling agent KH550, 3 parts of hydroxyapatite and 2 parts of sodium carboxymethyl cellulose to 6 parts of lanthanum chloride solution and stirring thoroughly, and the stirring is completed to obtain a modified solution; S12: The nano-titanium dioxide and the modified liquid are stirred and modified in a weight ratio of 2:5, the stirring temperature is 65° C., the stirring time is 1 h, the stirring speed is 500 r / min, and after the stirring is completed, the mixture is filtered and dried to obtain modified nano-titanium dioxide.
[0039] The mass fraction of the lanthanum chloride solution of the present embodiment is 6%.
[0040] The method for preparing a high heat-resistant plastic bottle of the present embodiment comprises the following steps: mixing the raw materials, then extruding and granulating them at an extrusion temperature of 165°C, and then blow molding them at a temperature of 120°C using hot air blow molding to obtain a high heat-resistant plastic bottle.
[0041] Example 3. A high heat-resistant plastic bottle of this embodiment includes the following raw materials in parts by weight: 30-35 parts of linear low-density polyethylene, 25-30 parts of recycled plastic raw materials, 10-15 parts of modified plant fibers, 4-7 parts of antibacterial agents, 2-5 parts of antioxidants, 3 parts of epoxidized soybean oil, and 3-6 parts of modified nano titanium dioxide.
[0042] The linear low-density polyethylene of this embodiment has a melt index of 50 g / 10 min at 190° C. and 2.16 kg; the antibacterial agent is nano silver powder; The recycled plastic raw material is waste plastic that has been recycled, then treated in a 5% by mass acid solution for 2 hours, then washed with boiling water for 3 times, and then crushed to 100 mesh; the antioxidant is antioxidant 1010; The preparation method of the modified plant fiber of this embodiment is: S1: adding 3.5 parts of nano magnesium oxide, 2.5 parts of boron nitride and 1.5 parts of calcium stearate to 6.5 parts of chitosan solution and stirring evenly to obtain nano magnesium oxide liquid; Plant fibers are added to nano magnesium oxide in a weight ratio of 2:5 and stirred to obtain a fiber-modified calcium carbonate solution; S2: The fiber-modified calcium carbonate solution and the co-mixing agent are mixed in a weight ratio of 5:3, and the mixture is ball-milled at a speed of 1500 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain the modified plant fiber.
[0043] The mass fraction of the chitosan solution in this embodiment is 3.5%; the stirring speed of the stirring treatment is 500 r / min, and the stirring is performed for 25 minutes.
[0044] The preparation method of the synergistic agent of this embodiment is: The silicon micropowder is immersed in a dopamine hydrochloride solution which is 3 times the total amount of the silicon micropowder to obtain a silicon micropowder liquid. The silicon micropowder liquid, tourmaline powder and sodium silicate solution are mixed in a weight ratio of 3:1:2 and ball-milled at a speed of 1500 r / min for 1 hour. After the ball milling is completed, the mixture is filtered and dried to obtain a synergistic agent.
[0045] The mass fraction of the dopamine hydrochloride solution in this embodiment is 3.5%; the mass fraction of the sodium silicate solution is 4%.
[0046] The modification method of the modified nano titanium dioxide in this embodiment is: S11: adding 1.5 parts of silane coupling agent KH550, 2.5 parts of hydroxyapatite and 1.5 parts of sodium carboxymethyl cellulose to 5.5 parts of lanthanum chloride solution and stirring thoroughly, and the stirring is completed to obtain a modified solution; S12: The nano-titanium dioxide and the modified liquid were stirred and modified in a weight ratio of 2:5, the stirring temperature was 62° C., the stirring time was 1 h, the stirring speed was 500 r / min, and after the stirring was completed, the mixture was filtered and dried to obtain modified nano-titanium dioxide.
[0047] The mass fraction of the lanthanum chloride solution of the present embodiment is 5%.
[0048] The method for preparing a high heat-resistant plastic bottle of the present embodiment comprises the following steps: mixing the raw materials, then extruding and granulating them at an extrusion temperature of 165°C, and then blow molding them at a temperature of 120°C using hot air blow molding to obtain a high heat-resistant plastic bottle.
[0049] Comparative Example 1. The difference from Example 3 is that no modified plant fiber is added.
[0050] Comparative Example 2. The difference from Example 3 is that no fiber-refining calcium carbonate solution is added in the preparation of the modified plant fiber.
[0051] Comparative Example 3. The difference from Example 3 is that no nano magnesium oxide solution is added in the preparation of the fiber-compounded calcium carbonate solution.
[0052] Comparative Example 4. The difference from Example 3 is that nano magnesium oxide and boron nitride are not added into the nano magnesium oxide liquid.
[0053] Comparative Example 5. The difference from Example 3 is that no synergist is added in the preparation of the modified plant fiber.
[0054] Comparative Example 6. The difference from Example 3 is that no silicon powder liquid is added to the co-formulating agent.
[0055] Comparative Example 7. The difference from Example 3 is that tourmaline powder and sodium silicate solution are not added to the co-formulating agent.
[0056] Comparative Example 8. The difference from Example 3 is that no modified nano titanium dioxide is added.
[0057] Comparative Example 9. The difference from Example 3 is that no modifying liquid is added to the modified nano titanium dioxide.
[0058] The performance of the products of Examples 1-3 and Comparative Examples 1-9 was tested under normal conditions. They were placed at 65°C for 1 hour and then at -5°C for 2 hours. The above was one cycle. The cycle test was repeated 10 times to test the thermal stability of the products. The test was as follows:
[0059] It can be seen from Comparative Examples 1-9 and Example 3 that the product of Example 3 has excellent compressive strength, impact toughness and antibacterial properties, the product can achieve coordinated improvement, and the product has a significant effect on heat resistance and stability; The present invention does not add one of modified plant fiber and modified nano titanium dioxide, and the performance of the product deteriorates significantly. The two are used in combination to achieve synergistic effects, and the product performance effect is obvious; In the preparation of the modified plant fiber, no fiber compounding calcium carbonate liquid is added, no nano magnesium oxide liquid is added, no nano magnesium oxide and boron nitride are added to the nano magnesium oxide liquid, no co-formulating agent is added, no silicon micropowder liquid is added to the co-formulating agent, and no tourmaline powder and sodium silicate solution are added to the co-formulating agent. The performance of the products tends to deteriorate. The modified plant fiber obtained by combining the co-formulating agent obtained by the specific method of the present invention with the fiber compounding calcium carbonate liquid has the most significant product performance effect. Other methods are not as obvious as the effect of the present invention. In addition, no modifying liquid is added to the modified nano titanium dioxide. The performance of the products tends to deteriorate. Only the modified nano titanium dioxide obtained by the specific method of the present invention has the most significant product performance effect.
[0060] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0061] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A high heat-resistant plastic bottle, characterized in that: It includes the following raw materials in parts by weight: 30-35 parts of linear low-density polyethylene, 25-30 parts of recycled plastic raw materials, 10-15 parts of modified plant fibers, 4-7 parts of antibacterial agents, 2-5 parts of antioxidants, 2-4 parts of epoxidized soybean oil, and 3-6 parts of modified nano titanium dioxide.
2. A high heat-resistant plastic bottle according to claim 1, characterized in that: The plastic bottle comprises the following raw materials in parts by weight: 30-35 parts of linear low-density polyethylene, 25-30 parts of recycled plastic raw materials, 10-15 parts of modified plant fibers, 4-7 parts of antibacterial agents, 2-5 parts of antioxidants, 3 parts of epoxidized soybean oil, and 3-6 parts of modified nano titanium dioxide.
3. A high heat-resistant plastic bottle according to claim 2, characterized in that: The linear low-density polyethylene has a melt index of (20-80) g / 10 min at 190° C. and 2.16 kg; the antibacterial agent is nano silver powder; The recycled plastic raw material is waste plastic that has been recycled, then treated in a 5% by mass acid solution for 2 hours, then washed with boiling water for 3 times, and then crushed to 100 meshes; the antioxidant is antioxidant 1010.
4. A high heat-resistant plastic bottle according to claim 1, characterized in that: The preparation method of the modified plant fiber is: S1: adding 2-5 parts of nano magnesium oxide, 2-3 parts of boron nitride and 1-2 parts of calcium stearate to 5-8 parts of chitosan solution and stirring evenly to obtain nano magnesium oxide liquid; Plant fibers are added to nano magnesium oxide in a weight ratio of 2:5 and stirred to obtain a fiber-modified calcium carbonate solution; S2: The fiber-modified calcium carbonate solution and the co-mixing agent are mixed in a weight ratio of 5:3, and the mixture is ball-milled at a speed of 1500 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain the modified plant fiber.
5. A high heat-resistant plastic bottle according to claim 4, characterized in that: The mass fraction of the chitosan solution is 2-5%; the stirring speed of the stirring treatment is 450-550 r / min, and the stirring time is 20-30 minutes; and the plant fiber is bamboo fiber.
6. A high heat-resistant plastic bottle according to claim 4, characterized in that: The preparation method of the synergistic agent is: The silicon micropowder is immersed in a dopamine hydrochloride solution which is 2-4 times the total amount of the silicon micropowder to obtain a silicon micropowder liquid. The silicon micropowder liquid, tourmaline powder and sodium silicate solution are mixed in a weight ratio of 3:1:2 and ball-milled at a speed of 1500 r / min for 1 hour. After the ball-milling is completed, the mixture is filtered and dried to obtain a synergistic agent.
7. A high heat-resistant plastic bottle according to claim 6, characterized in that: The mass fraction of the dopamine hydrochloride solution is 2-5%; the mass fraction of the sodium silicate solution is 3-5%.
8. The high heat-resistant plastic bottle according to claim 1, characterized in that: The modification method of the modified nano titanium dioxide is: S11: adding 1-2 parts of silane coupling agent KH550, 2-3 parts of hydroxyapatite and 1-2 parts of sodium carboxymethyl cellulose to 5-6 parts of lanthanum chloride solution and stirring thoroughly, and then completing the stirring to obtain a modified solution; S12: The nano-titanium dioxide and the modified liquid are stirred and modified at a weight ratio of 2:5, the stirring temperature is 60-65° C., the stirring time is 1 hour, the stirring speed is 450-500 r / min, and after the stirring is completed, the mixture is filtered and dried to obtain the modified nano-titanium dioxide.
9. A high heat-resistant plastic bottle according to claim 8, characterized in that: The mass fraction of the lanthanum chloride solution is 4-6%.
10. A method for preparing a high heat-resistant plastic bottle according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: mixing the raw materials, extruding and granulating them at an extrusion temperature of 165° C., and then blow molding them at a temperature of 120° C. by adopting a hot air blow molding method to obtain a plastic bottle with high heat resistance.